Rousseau, the Age of Enlightenment, and their legacies - Wokler, Robert, 1942-2006 (Princeton University Press, 2012)
Robert Wokler was one of the world's leading experts on Rousseau and the Enlightenment, but some of his best work was published in the form of widely scattered and difficult-to-find essays. This book collects for the first time a representative selection of his most important essays on Rousseau and the legacy of Enlightenment political thought. These essays concern many of the great themes of the age, including liberty, equality and the origins of revolution. But they also address a number of less prominent debates, including those over cosmopolitanism, the nature and social role of music and the origins of the human sciences in the Enlightenment controversy over the relationship between humans and the great apes.